Voluntary activation of trunk extensors appears normal in young adults who have recovered from low back pain. (25th February 2015) - Chiou, S.Y.; Jeevathol, A.; Odedra, A.; Strutton, P.H.
Abstract Background Low back pain (LBP) is associated with alterations in control of trunk movements and changes within central nervous system (CNS). Evidence shows that some of these alterations within the CNS are reversible when the symptoms are relieved, whereas other shows the opposite. Therefore, the purpose of the current study was to investigate whether alterations in voluntary activation (VA) of central neural drive, as assessed using twitch interpolation to measure VA, are present in subjects with a history of low back pain (HLBP), who are free from pain at the time of experiment. Methods Twelve adults with HLBP and 12 controls participated. Bilateral electromyographic recordings were obtained from erector spiane muscles at two vertebral levels (T12 and L4) and from rectus abdominis. Participants performed a series of brief isometric back extensions (50–100% maximum voluntary contraction) during which transcranial magnetic stimulation was delivered. The sizes of the evoked (superimposed) twitches were measured using dynamometry and VA was derived. The amplitude of motor evoked potentials (MEPs) and duration of cortical silent period (CSP) in erector spinae muscles were calculated; questionnaires were used to evaluate disability, levels of physical activity, quality of life and pain. Results The level of VA was not significantly different between HLBP and control groups. Additionally, there were no between‐group differences in the time‐to‐peak amplitudes of the twitches, MEP amplitudes or duration of CSP. Conclusions The ability to voluntarily activate back extensor muscles maximally does not appear to be impaired in subjects with a history of LBP during pain‐free episodes.